Prevalence of Hearing and Visionabnormalities in School Children in Udupi District Karnataka (Medico Legal Update, 2020)
Background: Preschool screenings are recommended for early detection and treatment of childhood visualand hearing disorders.Objective: To evaluate the prevalence of hearing abnormalities, visual impairments and correlate itsassociation with consumption of vitamin A rich food and usage of electronic devices in school going childrenin Udupi district, KarnatakaMethod: Rinnie’s test and Weber’s tests was done by using tuning fork method for hearing, Snellen’s chartfor distant vision, Jager’s chart for near vision, Ishiara chart for colour vision and confrontation test for fieldof vision. Questionnaires were used to get the detailed informations regarding consumption of vitamin Arich food and usage of electronic devices,Result: Screening test for hearing and vision conducted on 250 students. There was no significant hearingabnormality was found out of 250 students, there was hearing impairment in 1.6% of the children due toear infection. In vision screening,12.8% of children having visual abnormalities like myopia, hyperopia andcolor blindness. The total prevalence of vision abnormalities was 32(12.8%) 95% CI: 11.924-13.676.Conclusion: Vision and hearing screening is very essential in school children to recognize the visualimpairments or hearing abnormalities at earliest which will be helpful for further treatment. This studyshould be conducted in large sample size.